Potentialities and Challenges of Project-Based Method in Pedagogy - Rai, Shyam Kumar (DMC Journal, 2023)
Project based method is one of the most effective processes in pedagogy. Learning by doing theory is implemented by this method. The prime objectives of this study are to investigate the benefits and challenges of project based method and contribute in pedagogical process through new findings. Its findings will support to teachers to develop theirs professional skills and accordingly it helps to develop the learners’ intellectual as well as social skills. The target populations were selected from school students and campus lecturers for its findings. Purposeful sampling method was administered to select the sample population. Semi structured questionnaire, focused group discussion and observation were administered to collect the data from the respondents. Mixed approach is applied in this study. Previous literatures and present application condition of project method were methodologically analyzed. After its analysis, previous literatures and current application conditions of the project based method were traced similar.